Conjugation Inhibitors Effectively Prevent Plasmid Transmission in Natural Environments - Carolina Palencia-Gándara (American Society for Microbiology, 2021)
ABSTRACT Plasmid conjugation is a major route for the spread of antibiotic resistance genes. Inhibiting conjugation has been proposed as a feasible strategy to stop or delay the propagation of antibiotic resistance genes. Several compounds have been shown to be conjugation inhibitors in vitro, specifically targeting the plasmid horizontal transfer machinery. However, the in vivo efficiency and the applicability of these compounds to clinical and environmental settings remained untested. Here we show that the synthetic fatty acid 2-hexadecynoic acid (2-HDA), when used as a fish food supplement, lowers the conjugation frequency of model plasmids up to 10-fold in controlled water microcosms. When added to the food for mice, 2-HDA diminished the conjugation efficiency 50-fold in controlled plasmid transfer assays carried out in the mouse gut. These results demonstrate the in vivo efficiency of conjugation inhibitors, paving the way for their potential application in clinical and environmental settings. IMPORTANCE The spread of antibiotic resistance is considered one of the major threats for global health in the immediate future. A key reason for the speed at which antibiotic resistance spread is the ability of bacteria to share genes with each other. Antibiotic resistance genes harbored in plasmids can be easily transferred to commensal and pathogenic bacteria through a process known as bacterial conjugation. Blocking conjugation is thus a potentially useful strategy to curtail the propagation of antibiotic resistance. Conjugation inhibitors (COINS) are a series of compounds that block conjugation in vitro. Here we show that COINS efficiently block plasmid transmission in two controlled natural environments, water microcosms and the mouse gut. These observations indicate that COIN therapy can be used to prevent the spread of antibiotic resistance.